Education for Healthy Lifestyles through Exercise Education in Italian Prisons - Ario Federici; Salvatore Gabriele D'Alessio; Vahid Shoaei; Alessandro Capriotti (Pensa MultiMedia, 2022)
Prison has a general preventive purpose that aims to highlight the negativity of the crime committed. Re-education is not a guaranteed outcome, as the outcome of an educational process never is, but rather a 'bet' that society makes with itself on a possible, but never certain outcome. With motor activity, typical sedentary diseases (obesity, malabsorption syndrome, diabetes, cardiovascular diseases) are prevented. The social value of sporting activity must also be associated with this, as it stimulates socialisation, team spirit, respect for and sharing of rules, and the stimulus and motivation to achieve positive goals while respecting others. In this study, conducted on inmates of Fossombrone prison, the aim was to investigate the possible correlations between the level of physical activity, body image and well-being, and the role that physical activity plays within prison institutions. However, the idea is confirmed that physical activity for prisoners is very important both from a psycho-physical and re-educational point of view because it allows them to move and vent stress, conveys important values, teaches commitment to achieve objectives, increases self-esteem and improves lifestyle by limiting the onset of frequent pathologies found in prison facilities.